A EDUCAÇÃO DO CAMPO E A RELAÇÃO COM A IDENTIDADE LOCAL: reflexões a partir da escola São Tomé em Breves – Pará - COELHO, Helda Góes (2025)
This work deals with the relationship between field education and local identity, based on the teaching practice materialized at Escola São Tomé, in the municipality of Breves. Seeks to answer the following problem: Does the pedagogical practice materialized in the São Tomé Country School, in Breves no Marajó, contribute to the recognition of local identity and the identity strengthening of students, as citizens of the Marajoara Amazonian territory? The general objective is: To identify whether the pedagogical practice implemented in the locus school dialogues with the assumptions of the field education paradigm. In the methodological field, we have qualitative research involving the following procedures: bibliographic and documentary survey on Field Education; conducting semi-structured interviews with two teachers, a pedagogical coordinator, and three students from the fifth year of the institution; organization and analysis of data based on assumptions from the materialistic dialectical perspective. The empirical data obtained in dialogue with the theoretical basis pointed out that in the São Tomé school practices are developed that aim at the recognition of local identity and the identification of students with the field. However, there are obstacles and daily challenges that limit the teaching and education process in the field, among them: teacher education, the non-identification of the teacher (a) with the Field Education, the turnover of teachers, the lack of continuing education, the precarious infrastructure of the school and the lack of teaching resources and school transport. However, even with all the daily difficulties and obstacles, students like and feel good at school, and see themselves as subjects of the field. We conclude that the pedagogical practice materialized in the São Tomé school, in Breves contributes to the strengthening of the local identity and the identification of the students with the rural territory.